Neuroprotective Effects of Salidroside on Cerebral Ischemia/Reperfusion-Induced Behavioral Impairment Involves the Dopaminergic System - Zhong, Zhi-feng; Han, Jing; Zhang, Ji-Zhou; Xiao, Qing; Chen, Jing-yan; Zhang, Kai; Hu, Juan; Chen, Li-dian (Frontiers in Pharmacology, 2019)
Salidroside, a phenylpropanoid glycoside, is a main bioactive component of Rhodiola rosea L. Previous studies have indicated that salidroside has prominent anti-stroke effects in cerebral ischemia/reperfusion models. But the underline mechanisms involved are not well understood. This study was designed to illustrate the anti-stroke effects of salidroside on MCAO-induced models in rats and its potential mechanisms on dopaminergic system. We discovered that administration with salidroside increases dopamine (DA), 3, 4-dihydroxyphenylacetic acid (DOPAC) and high vanillin aldehyde acid (HVA) in real-time dynamic microdialysis using HPLC-ECD detection following transient ischemia. Meanwhile, we found that twice treatment with salidroside significantly ameliorated behavioral dysfunction, the motor functions after MCAO were assessed with neurological severity scores, balance beam test and foot fault test. Enzyme-linked immunosorbent assay (ELISA) suggested that MCAO-induce reduction in monoamine oxidase(MAO) was inhibited by salidroside. In addition, Immunohistochemical staining and immunofluorescence staining revealed a high level of TH in the ipsilateral striatum following cerebral ischemia/reperfusion, which could be further elevated by salidroside. Furthermore, we found that salidroside could reverse the immunoreactivity of TH in substantia nigra pars compacta (SNpc), which is composed of rich dopaminergic neurons projecting to the ipsilateral striatal caudate putamen (CPu) nucleus. These results suggest that the anti-stroke effects of salidroside on MCAO-induced cerebral ischemia/reperfusion may involve regulation of the neuronal circuits between the striatum and the SNpc by modulating monoamine metabolism, which may related to the promotion of dopaminergic system in brain.